Psychological interventions during COVID pandemic: Telehealth for individuals with cystic fibrosis and caregivers. Issue 7 (27th April 2021) - Graziano, Sonia; Boldrini, Francesca; Righelli, Dario; Milo, Francesco; Lucidi, Vincenzina; Quittner, Alexandra; Tabarini, Paola
Abstract: Introduction: Coronavirus disease 2019 (COVID‐19) emerged in China, leading to worldwide morbidity and mortality, including depression and anxiety. As the pandemic spread throughout Italy, mental health concerns increased for people with cystic fibrosis (pwCF), who are at greater risk. The aim was to pilot a Telehealth Psychological Support Intervention for pwCF and caregivers to reduce stress, depression, and anxiety during the lockdown in Italy in March 2020. Methods: This intervention utilized cognitive behavioral skills (e.g., cognitive reframing). Participants included 16 pwCF and 14 parents, who completed four individual telehealth sessions with a psychologist. Stress ratings, Patient Health Questionnaire and General Anxiety Disorder, PHQ‐8 and GAD‐7, were completed, in addition to Feasibility and Satisfaction ratings. Results: Ratings of stress significantly decreased from pre‐ to post‐testing for pwCF (paired t (14) = −4.06, p < .01) and parents (paired t = −5.2, p < .001). A large percentage of both groups scored in the clinical range for depression and anxiety at baseline (pwCF: depression/anxiety = 71%; parents: depression = 57%; anxiety = 79%); a large proportion (20%–40%) reported moderate to severe symptomatology. Significant reductions in depression for pwCF were found (pre: M = 8.0 to post: M = 4.7; paired t (14) = 2.8, p < .05) but not anxiety (pre: M = 6.9 to post: M = 5.6, t (14) = 1.2, p = NS—non‐significant). Parental depression decreased for parents (pre: M = 6.4 to post: M = 5.1, t (14) = −2.5, p < .05), but not anxiety (pre: M = 8.1 to post: M = 7.9, t (14) = −0.2, p = NS). Feasibility and Satisfaction were positive. Conclusion: This telehealth intervention yielded reductions in stress and depression for participants. Anxiety did not significantly decrease, possibly because COVID was ongoing. This feasible, satisfactory intervention was effective for improving mental health.